The role of the nurse in assisting women victims of sexual violence in Brazil (Research, Society and Development, 2022)
This study aimed to describe the role of the nurse in assisting women victims of sexual violence in Brazil. This was an integrative literature review carried out through virtual library searches: Biblioteca Virtual de Saúde (BVS) y Scientific Electronic Library Online (Scielo). Original articles published from 2012 onwards were included. The results indicate that sexual violence against women in Brazil is more prevalent in young women. Evidence shows that the nursing professionals felt incapable to carry out the reception, the approach and the care provision of the victims. At times nurses did not properly follow the specific protocols of care, resulting in failure in the referral of cases. As part of the multiprofessional health team, nurses play a leading role in the care of women victims of violence and, therefore, they must be adequately trained. Professional qualification is essential in the face of this assistance that results in effective nursing care that actually responds to the needs of victims, guaranteeing humanization and safety during care.